Distribusi dan Karakteristik Mikroplastik pada Daging dan Saluran Pencernaan Ikan Tongkol (Euthynnus affinis) di PPI Ujong Baroh, Aceh Barat : Distribusi dan Karakteristik Mikroplastik pada Daging dan Saluran Pencernaan Ikan Tongkol - Ika Kusumawati Kusumawati; Mai Suriani; siti rahayuning putri; Dini Islama (Talenta Publisher, 2026)
The increasing use of plastic in coastal areas has led to the accumulation of microplastic particles in marine environments, which can enter the food chain and pose risks to both aquatic organisms and humans as final consumers. Microplastics, defined as plastic particles smaller than 5 mm, originate from the degradation of larger plastics due to ultraviolet exposure and anthropogenic activities such as fishing, industrial waste, and household garbage. This study aimed to analyze the concentration, types, and polymer characteristics of microplastics in the flesh and digestive tract of mackerel tuna (Euthynnus affinis) caught by fishermen at PPI Ujong Baroh, West Aceh. The research was conducted from August to September 2024 using a purposive sampling method. Six fish samples were collected, and their flesh and digestive tract were digested using 10% KOH solution to remove organic matter. The filtrate was filtered with Whatman filter paper (1.6 µm) and observed under an optical microscope to identify the shape and color of microplastics. Fourier Transform Infrared (FTIR) spectroscopy was used to identify the polymer type. The results revealed five microplastic forms: fiber, fragment, film, pellet, and foam. Fiber was the most dominant, with an average abundance of 73.05 particles/gram in flesh and 42.83 particles/gram in the digestive tract. FTIR analysis confirmed that the dominant polymer was Polyamide (Nylon), which is commonly used in fishing nets and ropes. These findings indicate that microplastic contamination has occurred in fish consumed by coastal communities in West Aceh, reflecting the growing marine pollution problem in Indonesia. This study highlights the importance of strengthening marine waste management and monitoring seafood safety to reduce potential health and ecological impacts.